Proton 3S Task Track: task management system using Nielsen’s Heuristics / Nur Diyana Afini Roslan - Roslan, Nur Diyana Afini (2025)
Proton 3S Task Track is a management information system developed with Nielsen's Usability Heuristics, which tries to improve the efficiency of Proton's Sales Advisors (SAs) in customer order and performance management tasks. A case study was conducted at Proton 3S Goh Family Motors which discover the problems of fragmented task management, communication gaps, and lack of real-time updates. The project began with a comprehensive analysis of performance management systems in the automotive industry, followed by interviews and extensive research involving Proton SAs to ascertain the specific needs and requirements. As a result, the resultant system now incorporates in book management, task tracking, and performance monitoring in efforts to streamline communications and collaboration among members of the teams. Using the modified Waterfall model, the project proceeded through requirement analysis, system design, development, and testing. System evaluation was carried out in three categories of testing. The usability testing was done with 30 users and returned the highest mean score of 4.5/5 for the functionality and navigation which is both labelled intuitive. While reliability, Jakob’s Nielsen’s Usability Heuristics and system interface were also accorded high scores, they were rated at 4.4 out of 5, 4.47 out of 5, and 4.4 out of 5, respectively. Expert feedback pointed to the strengths of the system in improving operational efficiency, but they recommended integration with advanced analytics, real-time notifications, and increased the scalability. Their feedback was incorporated toward improving the system's performance.